Impurity diffusion in ion implanted AlN layers on sapphire substrates by thermal annealing. (1st February 2022) - Okumura, Hironori; Watanabe, Yasuhiro; Shibata, Tomohiko; Yoshizawa, Kohei; Uedono, Akira; Tokunaga, Hiroki; Koseki, Shuuichi; Arimura, Tadanobu; Suihkonen, Sami; Palacios, Tomás
Abstract: We report on impurity diffusion in ion implanted AlN layers after thermal annealing. Silicon, tin, germanium, and magnesium ions were implanted into single-crystal Al-polar AlN layers grown on sapphire substrates. By annealing at 1600 °C, silicon and magnesium atoms were diffused in the AlN layer, while less change was observed in the distribution of germanium atoms. Silicon implantation introduced vacancy-related defects. By annealing at temperatures over 1300 °C, the vacancy-related defects were reduced, while oxygen atoms were diffused from the substrate due to sapphire decomposition. We reproducibly achieved silicon-implanted AlN layers with electrical conductance by controlling the annealing temperature and distribution of silicon and oxygen concentrations.